2017
DOI: 10.4209/aaqr.2016.11.0482
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Sources of Atmospheric Polycyclic Aromatic Hydrocarbons at an Industrial Region in Kaohsiung, Taiwan

Abstract: The chemical mass balance model was applied to estimate the major sources of atmospheric polycyclic aromatic hydrocarbons (PAHs) at an Industrial Region in Kaohsiung, Taiwan. The gaseous and particulate phases of 16 individual compounds were analyzed between March 2012 and August 2012. The mean total concentrations and total BaP eq were higher during the cold season and lower during the warm summer, with gaseous PAHs predominant at all sites. Low weight-PAHs and median weight-PAHs were found predominantly in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 31 publications
(51 reference statements)
1
15
0
Order By: Relevance
“…Normally, PAHs in the atmosphere are emitted from combustion of organic matters used for different industrial processes and energy production, vehicular traffic, incineration of refuse burning, biomass burning and residential heating (Ravindra et al, 2006;Liu et al, 2016;Lai et al, 2017). PAHs with two to three rings (LMW: low molecular weight) are generally present in the gas phase under normal atmospheric conditions, whereas, PAHs with four to seven rings (HMW: high molecular weight) are mostly adsorbed on particle surfaces due to their low vapor pressure in particulate phase, especially in cold seasons (Tsapakis and Stephanou, 2005;Chen et al, 2016;Amarillo et al, 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Normally, PAHs in the atmosphere are emitted from combustion of organic matters used for different industrial processes and energy production, vehicular traffic, incineration of refuse burning, biomass burning and residential heating (Ravindra et al, 2006;Liu et al, 2016;Lai et al, 2017). PAHs with two to three rings (LMW: low molecular weight) are generally present in the gas phase under normal atmospheric conditions, whereas, PAHs with four to seven rings (HMW: high molecular weight) are mostly adsorbed on particle surfaces due to their low vapor pressure in particulate phase, especially in cold seasons (Tsapakis and Stephanou, 2005;Chen et al, 2016;Amarillo et al, 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…profiles of PAHs for various identified sources were adopted from relevant literature (Raiyani et al, 1993;Khalili et al, 1995;Lee and Kim 2007;Bi et al, 2008;Park et al, 2013;Kong et al, 2013;USEPA, 2016;Lai et al, 2017). We considered an uncertainty of 20% for all ambient concentrations and source profiles of individual PAH compounds during simulation on the platform of CMB8.2 model (Lai et al, 2017). Looking at the past trends of research reported in the literature, several studies in developing countries have used the source profiles of both developing and developing countries (Hanedar et al, 2011;Teixeira et al, 2015;Bortey-Sam et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…PAHs can be generated from pyrogenic, petrogenic, biogenic, or diagenetic (indoor/outdoor) sources (Kavouras et al, 2015;Mwangi et al, 2015;Stogiannidis and Laane, 2015;Zhang et al, 2016;Fan et al, 2017;Lai et al, 2017;Li et al, 2017). In our previous works, we reported the emissions of 21 PAHs from a H 2 -O 2 PEMFC (installed by a lab-prepared MEA with the same Pt loading of 0.5 mg cm -1 on anode and cathode) (Huang et al, 2015) and effect of operating conditions on PAHs emission from the PEMFC (Huang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) are a class group of complex organic compounds containing hydrogen and carbon and constituted fused ring structure including at least two linear or cluster benzene rings (Pongpiachan, 2016;Lai et al, 2017). PAHs originated from both natural (forest fires, volcanic eruptions and etc.)…”
Section: Introductionmentioning
confidence: 99%